2016
DOI: 10.1097/igc.0000000000000652
|View full text |Cite
|
Sign up to set email alerts
|

Matrix Metallopeptidase 14 Plays an Important Role in Regulating Tumorigenic Gene Expression and Invasion Ability of HeLa Cells

Abstract: Matrix metallopeptidase 14 plays an important role in regulating invasion of HeLa cells. Matrix metallopeptidase 14 knockdown contributes to attenuating the malignant phenotype of cervical cancer cell.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
1
2
0
Order By: Relevance
“…Furthermore, we examined the expression of MMP14 in 60 cervical cancer tissues and 60 adjacent normal tissues. The expression of MMP14 in cervical cancer tissues was much higher than in normal cervical tissues (Figure 3(e,f)), indicating that high expression of MMP14 is associated with cervical cancer, which was consistent with other researchers [22,26]. These data indicate that the CCAT1 expression level is negatively correlated with miR-181a-5p and further regulates the expression of MMP14.…”
Section: Ccat1 Regulates the Expression Of Mir-181a-5p And Matrix Metsupporting
confidence: 89%
See 1 more Smart Citation
“…Furthermore, we examined the expression of MMP14 in 60 cervical cancer tissues and 60 adjacent normal tissues. The expression of MMP14 in cervical cancer tissues was much higher than in normal cervical tissues (Figure 3(e,f)), indicating that high expression of MMP14 is associated with cervical cancer, which was consistent with other researchers [22,26]. These data indicate that the CCAT1 expression level is negatively correlated with miR-181a-5p and further regulates the expression of MMP14.…”
Section: Ccat1 Regulates the Expression Of Mir-181a-5p And Matrix Metsupporting
confidence: 89%
“…The matrix metalloproteinase (MMP) family proteins are involved in the breakdown of extracellular matrix in normal physiological processes, such as embryonic development, reproduction, and tissue remodeling, as well as in disease processes. MiR-181a-5p is reported to inhibit cell proliferation and invasion by downregulating MMP14 [22,26]. Additionally, MMP14 activity mediates the proteolytic processing and activation of heparin-binding EGF-like growth factor (HB-EGF), stimulating the EGFR signaling pathway to increase proliferation and tumor growth [23], which was related with cervical cancer [44,45].…”
Section: Discussionmentioning
confidence: 99%
“…MMP14 positive expression is considered to connect with a high recurrence of CC patients [10]. And MMP14 down-regulation was found to impair the proliferation and invasion ability of CC cells [26]. Correspondingly, the CCK-8 assay and transwell assay in our study indicated that MMP14 inhibition by miR-195-5p led to a poor proliferation and invasion profile of CC cells.…”
Section: Cellular Physiology and Biochemistry Cellular Physiology Andmentioning
confidence: 71%